General and Life-Domain Procrastination in Highly Educated Adults in Israel - Hen, Meirav; Goroshit, Marina (Frontiers in Psychology, 2018)
Procrastination is usually perceived as a general behavioral tendency, and was studied mostly in college students in academic settings. Recently there is a growing body of literature to support the study of procrastination in older adults and in different life-domains .Based on these advances in the literature, the present study examined procrastination in 430 highly educated adults in Israel. Findings showed that respondents reported significantly higher procrastination in maintaining health behaviors and spending leisure time rather in other life-domains. Forty percent of participants reported high procrastination in health behaviors, while only 9.5% reported this level of procrastination in parenting and 1% in the general tendency to procrastinate. Further findings suggested that 25% of respondents reported high procrastination in four or more life-domains, and 40% - in one to three life-domains. The general tendency to procrastinate was moderately associated with procrastination in finance, education and career life-domains and weekly with other life-domains. Fourteen percent of participants reported that procrastination influenced their life the most in health behaviors, 12 % in career and education and 11% in romance and family life. These initial findings contribute to the overall perspective of life-domain specificity of procrastination in adults, and emphasize the importance to further study and develop a life-span perspective.